The role of EGFR‐TKIs as adjuvant therapy in EGFR mutation‐positive early‐stage NSCLC: A meta‐analysis. Issue 7 (4th March 2021) - Lin, Chutong; Hu, Fengling; Chu, Hongling; Ren, Peng; Ma, Shanwu; Wang, Jingdi; Bai, Jie; Han, Xuan; Ma, Shaohua
Abstract: Background: The role of adjuvant epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) is not clear in early‐stage nonsmall‐cell lung cancer (NSCLC) patients. This meta‐analysis aims to compare the efficacy and safety of EGFR‐TKIs as adjuvant therapy with chemotherapy or placebo in NSCLC patients harboring EGFR mutations. Patients and Methods: Pubmed, Embase, and Cochrane databases were searched for randomized controlled trials. The hazard ratio (HR) of disease‐free survival (DFS) and overall survival (OS) as well as the risk ratio (RR) of severe adverse events were merged. Results: Seven articles from five studies from 1843 records, a total of 1227 patients, were included in the analysis. The HR for DFS was 0.38 (95% confidence interval [CI] 0.22–0.63), in favor of EGFR‐TKIs. However, no significant benefit of OS was seen (HR = 0.61, 95% CI 0.31–1.22). Treatment benefit was more pronounced in patients with advanced disease stage and longer duration of medication, EGFR exon 19 deletion mutation, and treatment with third‐generation EGFR‐TKIs. Adjuvant targeted therapy may cause few adverse events compared with chemotherapy (RR = 0.28, 95% CI 0.09–0.94). The possibility of severe adverse events for the first‐generation drugs was significantly lower than for third‐generation drugs. Conclusion: In EGFR mutation‐positive patients with stage IB–IIIA NSCLC, compared with adjuvant chemotherapy or placebo, adjuvant EGFR‐TKIs should effectively improve the patient's DFS, but not effectively improve OS. Disease stage, treatment duration, mutation types, and therapeutic drugs could affect the degree of benefit. Adjuvant EGFR‐TKIs had more favorable tolerability than chemotherapy, especially with the usage of first‐generation drugs. Abstract : In EGFR mutation‐positive patients with stage IB–IIIA NSCLC, compared with adjuvant chemotherapy or placebo, adjuvant EGFR‐TKIs should effectively improve the patient's DFS, but not effectively improve OS.